Electromyographic diagnosis of multifocal pyomyositis. Issue 2 (23rd December 2014) - Spolter, Yonatan S.; Katirji, Bashar; Preston, David C.
ABSTRACT Introduction: Multifocal pyomyositis is a rare inflammatory myopathy caused by bacterial infection and abscess formation in multiple skeletal muscles. To date, electromyography (EMG) of pyomyositis has not been reported. Methods: We describe the EMG findings of a patient with pathologically proven multifocal pyomyositis. Results and Conclusions: Muscles affected by pyomyositis demonstrate EMG features similar to those of other inflammatory myopathies. Other features such as acute entrapment neuropathy may exist concomitantly due to nerve compression from muscle abscess formation. Muscle Nerve 51: 293–296, 2015